Preliminary Study on the Impact of Ruminal Ciliate Inoculation in Fauna-Free Conditions on the Ruminal Fermentation and Ciliate–Prokaryote Association In Vitro - Geonwoo Kim; Woohyung Lee; Tansol Park (Fermentation)
Ruminants rely on the rumen for the anaerobic fermentation of fibrous plant materials, facilitated by a complex microbial community of bacteria, archaea, fungi, and ciliates. Among them, ruminal ciliates significantly influence ruminal fermentation, methane production, nitrogen utilization efficiency, and microbial interactions. This study examined the impact of ciliate inoculation on ruminal fermentation, microbial composition, and functional profiles in fauna-free conditions. Six treatments were tested: control (no ciliates), small entodinia, Epidinium spp., isotrichids, Ophryoscolex spp., and a mixed inoculum. Using QIIME2 to analyze 16S rRNA gene sequences, the study revealed group-specific effects on methane production, volatile fatty acids (VFAs), and microbial diversity. Small entodinia inoculation increased Streptococcus abundance, while isotrichids enriched Megasphaera, enhancing butyrate production. Alpha diversity indices indicated reduced richness in the ciliate-inoculated groups, reflecting predation on prokaryotes. Beta diversity showed distinct microbial and functional profiles among the treatments. Functional analysis highlighted elevated glycerolipid metabolism in isotrichid groups, associated with Bacteroides and Megasphaera, suggesting roles in lipid metabolism and oxidative stress resistance. Despite limited ciliate cell counts, the study emphasizes ciliate-specific interactions and the role of lactic acid-associated bacteria in shaping ruminal fermentation.